Students’ Learning Characteristics, Perceptions of Small-Group University Teaching, and Understanding Through a “Meeting of Minds” - Karagiannopoulou, Evangelia; Entwistle, Noel (Frontiers in Psychology, 2019)
Previous research has described some of the main characteristics of university teachers who teach in different ways, using a variety of methods and conceptions. What is generally missing from previous research is the impact of contrasting teaching approaches on students with different learning characteristics. The present investigation builds on a previous case study that identified the potential influence of a ‘meeting of minds’ between tutors and students in developing personal understanding, and also suggested contrasting perceptions of differing forms of teaching. Twenty-one in-depth interviews were used to identify distinctive perceived ways of teaching and groups of students with contrasting learning intentions, looking in particular at the perceptions of tutors who were seen to encourage a ‘meeting of minds’. The main characteristics of these tutors were found be tolerating ambiguity, showing authenticity and empathy, which led to providing opportunities for discussion in breaks, and offering thinking spaces within class. The analyses identified contrasting perceptions of teaching among students who differed in their learning characteristics, and suggested how cognitive and affective elements in students’ experiences of teaching might be intertwined in influencing the development of personal understanding.